SANTUN BERBAHASA CERMIN KARAKTER BANGSA - Lestari, Dewi (Lentera: Jurnal Ilmiah Kependidikan, 2017)
Language has an ability to create the characteristic of human being in Indonesia language consist of the positive power to make the beautiful crystal and improving the crystal it’s self. The wreaters hope to the reader in order to they can understand and can be implemented. The characters of education using the power of language and then the positive energy of it’s can give some supplement to improve the human being of Indonesia characteristic.